KREATIVITAS LOEDIRO PANTJOKO DALAM TARI REWANDA WIRAKA KRIDO - Oktaviantari, Hervina; Suharji, Suharji (Greget: Jurnal Kreativitas dan Studi Tari, 2024)
The research entitled "Rewanda Wiraka Krido Dance by Loediro Pantjoko" examines two problems raised in the research, namely (1) what is the form of the Rewanda Wiraka Krido dance by Loediro Pantjoko; and (2) how creative Loediro Pantjoko is in the Rewanda Wiraka Krido Dance. Two problems were studied using Y. Sumandiyo Hadi's theory of choreography and then to reveal creativity using Srihadi's concept. Choreography theory is a framework of thought used to analyze, interpret and create dance works. By using this theory, you can reveal the meaning contained in a dance, understand the creative process of its creator, and evaluate its aesthetic and artistic qualities. This research uses qualitative methods, the data collection stage is produced through observation, interviews, literature study and document study.The research results obtained show that choreographically the Rewanda Wiraka Krido Dance is a group of monkeys that live and thrive in the wilderness. The Rewanda Wiraka Krido dance uses developmental movement motifs from the Surakarta Style Traditional Dance combined with acrobatic movements. The addition of female dancers is a new breakthrough so that they can be accepted throughout society. Creativity is created based on sensitivity to the environment, life experience and imagination, so that he succeeded in presenting Rewanda Wiraka Krido's choreography with totality. Java has a wealth of traditional dances with various themes and meanings. The word "Wira" in Javanese is often associated with courage and heroism, while "Krido" can be interpreted as a game or performance. This combination of words may indicate a dance that tells a heroic story.